2015
DOI: 10.1155/2015/601426
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Conducted Emissions in Satellite Power Buses

Abstract: This work reports a modeling methodology for the prediction of conducted emissions (CE) in a wide frequency range (up to 100 MHz), which are generated by dc/dc converters and propagate along the power buses of satellites. In particular, the dc/dc converter seen as a source of CE is represented by a behavioral model, whose parameters can be identified by two unit-level experimental procedures performed in controlled test setups. A simplified multiconductor transmission-line (MTL) model is developed to account f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 5 publications
0
36
0
Order By: Relevance
“…It was shown that frequency-domain circuit simulation can be used to predict the filter IL for arbitrary load and line impedances. In perspective, this opens the way to the assessment of filter performance through broadband linear models of CE sources and loads [3]- [6]. The full potential of the proposed technique becomes explicit when modeling of EMI filters is to be run in combination with nonlinear, time-variant power-electronic systems, through component-level representations and time-domain circuit simulation [1], [7]- [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that frequency-domain circuit simulation can be used to predict the filter IL for arbitrary load and line impedances. In perspective, this opens the way to the assessment of filter performance through broadband linear models of CE sources and loads [3]- [6]. The full potential of the proposed technique becomes explicit when modeling of EMI filters is to be run in combination with nonlinear, time-variant power-electronic systems, through component-level representations and time-domain circuit simulation [1], [7]- [10].…”
Section: Discussionmentioning
confidence: 99%
“…For effective characterization of power-electronic equipment as CE sources in the frequency domain, experimental methods to identify approximate, linear behavioral models composed of frequency-dependent impedances and sources were presented in [3], [4]. Together with circuit representations of lineimpedance stabilization networks (LISNs), energy sources, lumped or distributed-parameter models of cables, these frequency-domain techniques proved to be effective for CE analysis in complex systems [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…For the sake of modelling, the behavioral model in [25,26] is exploited for the dc-dc converter. Accordingly, the active part of the converter is represented by means of two current sources (connected between each wire in the power line and ground), whose frequency spectra are exacted from measurement data.…”
Section: Description and Modelling Of The Test Setupmentioning
confidence: 99%
“…Moreover, the passive part of the converter is modelled by a 2 × 2 matrix of admittances, whose frequency response (not reported here for the sake of brevity) was retrieved from the scattering parameters measured at the input pins of the dc-dc converter switched off. : Frequency spectra of the equivalent current sources S1 , S2 modelling the active part of the dc-dc converter [25,26].…”
Section: Description and Modelling Of The Test Setupmentioning
confidence: 99%
“…Actually, the impact of long-cable effects is fundamental in CE analysis of inverter-fed motor systems [5,[10][11][12], as well as other powerelectronics devices such as dc/dc converters in space satellites [19,20]. A quantitative estimation of the impact of the length of the dc power bus can be exemplified here by exploiting the proposed model.To this aim, the length of the dc power bus in Fig.…”
Section: Impact Of the Length Of The DC Power Busmentioning
confidence: 99%